Resource budget for workface planning in industrial-construction. Issue 5 (26th February 2019) - Siu, Ming Fung Francis
Abstract : Purpose: The purpose of this paper is to develop a novel analytical approach for workface planning practice in industrial-construction sector such that the construction work package (CWP) resource budget can be sufficiently planned for delivering possible field installation work package (FIWP) schedules with work uncertainty. Design/methodology/approach: The relationship between CWP resource budget and FIWP schedules is first elucidated based on workface planning practice. The literature of work packaging, workface planning and project scheduling is reviewed. A novel analytical approach is then developed to quantify CWP resource budget based on a probability theory, in consideration of the probability of occurrence of feasible FIWP schedules formulated based on a resource scheduling approach. The results of case studies given by the new approach are cross validated by using simulation and optimization techniques. Findings: The new analytical approach can assist workface planning by quantifying the expected CWP resource budget to deliver the FIWP work scope with certain activities that are planned at project level and with uncertain activities that are found at workface level. Practical implications: The new analytical approach helps project and workface planners to reliably deploy CWP resource budget for delivering FIWP schedules instead of guessing the budget based on experience. An industrial-construction project for upgrading oil-sands refinery facility is used to show the practical implications. Originality/value: This research develops a new analytical approach for workface planning practice to determine sufficient CWP resource budget for delivering feasible FIWP schedules with work uncertainty.